Mechanisms of disease: inflammasome activation and the development of type 2 diabetes - Grant, Ryan W.; Dixit, Vishwa D. (Frontiers in Immunology, 2013)
Over the recent past, the importance of aberrant immune cell activation as one of the contributing mechanisms to the development of insulin-resistance and type 2 diabetes (T2D) has been recognized. Among the panoply of pro-inflammatory cytokines that are linked to chronic metabolic diseases, new data suggests that interleukin-1β (IL-1β) may play an important role in initiating and sustaining inflammation induced organ dysfunction in T2D. Therefore, factors that control secretion of bioactive IL-1β have therapeutic implications. In this regard, the identification of multiprotein scaffolding complexes, ‘inflammasomes’, has been a great advance in our understanding of this process. The secretion of bioactive IL-1β is predominantly controlled by activation of caspase-1 through assembly of a multiprotein scaffold, ‘inflammasome’ that is composed of NLRP3 (for nucleotide-binding domain, leucine-rich–containing family, pyrin domain–containing-3) ASC (apoptosis associated speck-like protein containing a CARD) and procaspase-1. The NLRP3 inflammasome appears to be an important sensor of metabolic dysregulation and controls obesity-associated insulin resistance and pancreatic beta cell dysfunction. Initial clinical “proof of concept” studies suggest that blocking IL-1β may favorably modulate factors related to development and treatment of T2D. However, this potential therapeutic approach remains to be fully substantiated through phase-II clinical studies. Here, we outline the new immunological mechanisms that link metabolic dysfunction to the emergence of chronic inflammation and discuss the opportunities and challenges of future therapeutic approaches to dampen NLRP3 inflammasome activation or IL-1β signaling for controlling type 2 diabetes.